Modification of liposomes composed of a cationic lipid TMAG and an anionic lipid DSPG with a PEGylated lipid based on the investigation of lipid structures - Hohokabe M. (2023)
Charged lipids are widely utilized in functional liposomes for controlled release and targeting of drugs. In this study, we prepared the liposomes composed of a cationic lipid N-(α-trimethylammonioacetyl)-distearoyl-D-glutamate chloride (TMAG) and an anionic lipid 1,2-dioctadecanoyl-sn-glycero-3-phospho-1′-rac-glycerol (DSPG) with the molar ratio of TMAG/DSPG = 0:10–10:0 by hydration and extrusion methods. SAXS study for the lipid thin films revealed the formation of lamellar structures of TMAG and DSPG. The lipid thin film, except for the composition of 5:5 and 6:4, formed a liposome with a size of ∼100 nm that could encapsulate riboflavin in the inner aqueous phase. The zeta potentials of liposomes with the composition of 0:10–4:6 showed negative charges, while those of 7:3–10:0 showed positive charges. As the composition approached from 0:10 or 10:0 to 5:5, the phase transition temperature of the lipid bilayer from liquid crystalline phase to gel phase became higher, and the extent of fluorescence anisotropy increased. Thus, the lipid bilayer around the equimolar mixture could form a rigid structure with low fluidity of lipid alkyl chains. The surface charge cancellation by the opposite ionic head groups and the less curvature of the rigid lipid bilayer should prevent the liposomal formation at the composition of 5:5 and 6:4. However, the equimolar composition of 5:5 could form a liposome by the modification of distearoylphosphatidylethanolamine-polyethyleneglycol 2000 (DSPE-PEG2000) into the lipid bilayer at the molar ratio of 4% because it can reduce the rigidity of the lipid bilayer, provide positive curvature to the lipid bilayer, and stabilize the liposome dispersion in water through steric hindrance.